Incidence of Electrolyte Disturbance after TURP Procedure - Krisna, Daniel Mahendra; Maulana, Akhada (PT. Kalbe Farma Tbk., 2018)
Introduction. Trans Urethral Resection of the Prostate (TURP) as a gold standard treatment for benign prostatic hyperplasia (BPH) is performed with fluid irrigation that may cause electrolyte disturbance due to excessive fluid absorption; and may lead to increased mortality. This study is to determine the incidence of electrolyte disturbances and risk factors in TURP procedure. Materials & Methods. A descriptive retrospective study was conducted at Bhayangkara Hospital Mataram in January 2014-January 2016. The subjects were all BPH patients who underwent TURP surgery. Data were retrieved from medical records. All TURP procedures used distilled water as irrigation fluid. Presurgery and postsurgery electrolyte level, digital rectal grading and weight of resection tissue were recorded. Deranged electrolyte was defined as presence of any or both serum sodium < 130 or > 145 mmol/L and serum potassium <3,5 or > 5,5 mmol/L. Student’s T-test was applied to determine significant change between pre and post surgery variables. Results. Of 32 subjects, the mean age was 63.39 years and the mean weight of resected tissue was 63.03 grams. Sodium, potassium, chloride, and hemoglobin level were decreased post surgery (mean reduction 2.00, p = 0.000; 0.25, p = 0.000 ; 27.81, p = 0.021;1.050, p = 0.025, respectively). In 10 subjects, only significant decreased serum chloride and hemoglobin were found (mean reduction 4.5, p = 0.017; 1.46, p = 0.048, respectively). Sodium and potassium serum level were significantly decreased in non deranged electrolyte group (mean reduction 1.8, p = 0.01; 0.27, p = 0.00, respectively). No significant correlation between electrolyte imbalance with age and digital rectal examination grading. Conclusion. Electrolyte serum levels were significantly decreased after TURP procedure.Latar Belakang. Trans Urethral Resection of the Prostate (TURP) adalah suatu prosedur reseksi jaringan prostat, membutuhkan irigasi yang dapat menimbulkan gangguan elektrolit dan hemodinamika karena absorbsi cairan melalui vena selama irigasi. Gangguan elektrolit ini dapat meningkatkan morbiditas dan mortalitas. Tujuan penelitian ini adalah untuk mengetahui insidensi perubahan elektrolit dan faktor risikonya. Metode. Penelitian deksriptif retrospektif di Rumah Sakit Bhayangkara Mataram dengan subyek semua pasien BPH yang menjalani prosedur TURP pada periode Januari 2014- Januari 2016. Data sekunder diambil dari rekam medis yaitu kadar elektrolit pra bedah, kadar elektrolit pasca bedah, tingkatan BPH berdasarkan colok dubur. Semua prosedur TURP menggunakan air distilasi sebagai cairan irigasi. Gangguan elektrolit didefinisikan sebagai kadar natrium < 130 atau> 145 mmol/L atau kadar kalium <3,5 atau> 5,5 mmol/L. Student’s T-test digunakan uji kemaknaan perubahan pasca bedah. Hasil. Subyek 32 pasien, rerata usia 63.39 tahun dan rerata berat jaringan reseksi 63.03 gram. Terdapat penurunan kadar natrium, kalium, klorida, dan hemoglobin pasca bedah (rerata penurunan kadar serum Na 2.00, p = 0.000; serum K 0.25, p = 0.000 ; serum Cl 27.81, p = 0.021; dan serum Hb 1.050, p = 0.025). Terdapat 10 subyek dengan kategori gangguan elektrolit, klorida dan Hb signifikan (rerata penurunan kadar serum Cl 4.5, p = 0.017; dan serum Hb 1.46, p = 0.048). Pada kategori non gangguan elektrolit ditemukan penurunan natrium dan kalium yang signifikan (rerata penurunan kadar serum Na 1.8, p = 0.01; dan serum K 0.27, p = 0.00). Tidak ada korelasi dengan usia dan dengan tingkat penyakit berdasarkan colok dubur. Simpulan. Terdapat penurunan signifikan kadar elektrolit selama prosedur TURP.